El patrimonio gastronomico Salitreño y su aporte al turismo en el Recinto Santa Marianita - Bazurto Arevalo, Elvia Carolina (2020)
The present research project was developed in the Santa Marianita enclosure in the canton of Salitre with the aim of finding out how gastronomy influences the tourism sector, its contribution, supply and demand. Through the application of research methods and techniques, it was determined that the gastronomy offered in the canton has considerable acceptance due to its variety of typical dishes, many of which are cooked in a traditional way and attract the attention of tourists who visit this beautiful place from all over Ecuador. The field research through a survey of tourists aged between 15 and 60 years being 90% of national origin from both provinces and neighboring cantons who visit this natural spa which indicates that they are satisfied with the service received, but that if changes must be made in terms of infrastructure so that the merchants do not invade the river bank and the tourists transit freely, it was also found that there is no more energetic control over the volume of merchants, lack of training has influenced the failure of businesses by coinciding that they need more attention and a suitable place to work that allows them to offer an efficient service. The gastronomy has contributed in the economic development of the enclosure through the generation of employment in a direct and indirect way and as a new way to provide economic resources.